Anti‐Phased Miocene Ice Volume and CO2 Changes by Transient Antarctic Ice Sheet Variability. Issue 11 (24th November 2020) - Stap, L. B.; Knorr, G.; Lohmann, G.
Abstract: Geological evidence indicates large continental‐scale Antarctic ice volume variations during the early and mid‐Miocene. On million‐year timescales, these variations can largely be explained by equilibrium Antarctic ice sheet (AIS) simulations. In contrast, on shorter orbital timescales, the AIS needs not be in equilibrium with the forcing and ice volume variations may be substantially different. Here, we introduce a conceptual model, based on ice dynamical model results, to investigate the difference between transient variability and equilibrium differences of the Miocene AIS. In our model, an ice sheet will grow (shrink) by a specific rate when it is smaller (larger) than its equilibrium size. We show that phases of concurrent ice volume increase and rising CO2 levels are possible, even though the equilibrium ice volume decreases monotonically with CO2 . When the AIS volume is out of equilibrium with the forcing climate, the ice sheet can still be adapting to a relatively large equilibrium size, although CO2 is rising after a phase of decrease. A delayed response of Antarctic ice volume to (covarying) solar insolation and CO2 concentrations can cause discrepancies between Miocene solar insolation and benthic δ 18 O variability. Increasing forcing frequency leads to a larger disequilibrium and consequently larger CO2 ‐ice volume phase differences. Furthermore, an amplified forcing amplitude causes larger amplitude ice volume variability, because the growth and decay rates depend on the forcing. It also leads to a reduced average ice volume, resulting from the growth rates generally being smaller than the decay rates. Plain Language Summary: The early and mid‐Miocene (23–14 Myr ago) was the last period in Earth's history when the Antarctic ice sheet (AIS) size changed between being almost completely vanished and its current magnitude. So far, ice modelers have tried explaining this large‐scale AIS variability using steady‐state experiments, in which the final ice volume is in equilibrium with the forcing climate. In these simulations, phases of simultaneous ice sheet growth and CO2 increase have to be caused by increased precipitation outweighing increased melt in a warmer climate. Conversely, simultaneous ice sheet decay and CO2 decrease must be due to decreased precipitation exceeding decreased melt. Here, we provide an alternative explanation for these phases, based on the notion that the slowly evolving AIS is not in equilibrium with the forcing climate. In our model, an ice sheet will grow (shrink) by a specific rate when it is smaller (larger) than its equilibrium size. The AIS can then still be adapting to a relatively large equilibrium size, when CO2 is already increasing again after an initial drop. It can also continue decaying after a reversal from rising to sinking CO2 levels. Our results serve to aid the interpretation of Miocene geological oxygen isotope data. Key Points: Concurrent Antarctic ice sheet growth and CO2 level rise can occur because of disequilibrium between ice volume and climate The disequilibrium and CO2 ‐ice volume phase differences grow with increasing frequency of the forcing Larger amplitude CO2 variability causes larger amplitude ice volume variability and a smaller average ice sheet